Clinical symptoms, paraclinical tests and histopathological results in children with acute appendicitis in Zabol southeast of Iran: a cross-sectional study - Hesaraki, Mehran (International Journal of Research in Medical Sciences, 2017)
Background: This article aimed to assessment clinical signs and symptoms, paraclinical tests and histopathological results in children with acute appendicitis. Methods: A cross-sectional study conducted on 100 children with acute appendicitis in an urban hospital in southeast of Iran from January to December 2016. Participants were selected by simple random sampling method. Clinical signs and symptoms, paraclinical tests and histopathological results recorded in checklists. The data were analyzed using SPSS 22. Results: Mean age of the patients was 10.26±3.25, fourthly-eight of patients (58.5%) were males and 34 patients (41.5%) were females. The most frequent clinical signs and symptoms were acute suppurative appendicitis with peri appendicitis (45.83%) and acute suppurative appendicitis (39.58%). The most frequent results in ultrasound reports were Intestinal loop thickness greater than 6 mm without peristalsis (positive report) (46.34%) and Invisible appendix (nega Hesaraki tive report) (13.41%). Conclusions: The results of this study showed that abdominal pain and RLQ tenderness were the most common signs and symptoms and WBC left-shift was the most common laboratory finding. Since the rate of negative appendectomy in this study was consistent with surgical results and other articles, it is concluded that diagnostic accuracy of preoperative appendectomy was acceptable and most children with acute appendicitis underwent appendectomy.